‘UltraGUD LP’—ultrasound guided diagnostic LP—a randomizedcontrolled trial. Traditional landmark based lumbar puncture is as effective as ultrasound guided lumbar puncture in outpatient neurology settings - Renga, Vijay; Jeffreys, Charlotte A.; Tabasum, Afsha; MacKenzie, Todd A. (Frontiers in Neurology, 2025)
BackgroundLumbar puncture (LP) is a fundamental procedure in neurology, yet its success is influenced by patient anatomy and provider expertise. Ultrasound guidance has been shown to improve outcomes in emergency and anesthesia settings, but its effectiveness in outpatient neurology remains unclear.ObjectiveThis study (UltraGUD LP) aimed to compare the effectiveness of ultrasound-guided LP (US-LP) versus landmark-based LP (LM-LP) in an outpatient neurology setting, performed by a single experienced provider.MethodsA prospective randomized controlled trial was conducted from 2017 to 2022. Patients requiring LP were randomized to either LM-LP or US-LP. Success was defined as obtaining cerebrospinal fluid (CSF) within three attempts. Secondary outcomes included procedure time, incidence of traumatic taps, and post-LP headache rates.ResultsBoth techniques had comparable success rates, with LM-LP achieving 91% and US-LP 100% (p > 0.05). Procedure time was significantly shorter for LM-LP (13 vs. 19 min, p < 0.05). The incidence of traumatic taps and post-LP headaches was similar between groups.ConclusionIn a general outpatient neurology population, LM-LP is as effective as US-LP and requires less time. While US-LP may be beneficial for high-risk patients (e.g., obesity, prior back surgery), further studies are needed to confirm its superiority in these populations.